Clinical Characteristics and Mutation Profile in Patients with Carbonic Anhydrase II Deficiency: A Systematic Review of Case Reports - Rajkumar Kundavaram; Saswat Ranjan Raul; Vishnu Dev; Shruti Namdeo; Priya Gogia; Kirtisudha Mishra; Girish Chandra Bhatt (Indian Pediatrics Case Reports)
Background: Carbonic anhydrase II (CA II) deficiency is a rare autosomal recessive genetic disorder presenting with the characteristic triad of osteopetrosis, renal tubular acidosis (RTA), and intracerebral calcifications. However, the spectrum of mutations and clinical features varies. Objectives: A systematic review of case reports was done to describe the clinical spectrum and genetic mutations of children reported with carbonic anhydrase deficiency. Methods: A comprehensive search was done in major databases, using defined search terms. The identified reports underwent screening by different authors as per inclusion and exclusion criteria. Results: Twenty-two children (median age: 5 years) with genetically proven CA II deficiency were included, mostly males, all having RTA, classic triad being present in 64%. Over half of them had global developmental delay and one-third had vision and hearing defect, each. The most common mutation was c. 232 + 1 G >T, followed by del 12/ins4 at codon 211, seen in 9 (41%) and 4 (18%) children, respectively. Conclusion: Not all children with CA II deficiency present with triad, though RTA is present universally, c. 232 + 1 G >T being the most common variant in CA2 gene.